O olhar que distorce o tempo e o espaço: mitocrítica do discurso científico na teoria da relatividade - Silva, Samuel de Sousa (2014)
In this research, we observed how the scientific discourse, in this case the theory of relativity, was established as a persuasive discourse that posits not only truths about the workings of the cosmos, but states, above all, to himself as "the discourse of truth ". We demonstrate that the structure of persuasive discourse corresponds to the structure of mythic discourse and, therefore, the scientific discourse of Relativity Theory consists of a myth that structure. In this research, we reread the fundamental concepts of the theory of relativity, namely the concepts of time and space, and how the exaltation of the figure of the observer puts it, in the sphere of natural science, philosophical questions that mirror the human anguish. Thus, the scientific discourse of the Theory of Relativit y is guided by the same motivational guidelines of the mythic discourse. We postulate that science, as the myth, are speeches own of the curious mindset developed by mankind seeking to satisfy their need for knowledge, creating methodologies and epistemologies able to produce them. Thus, both the mythical and the scientific discourse are answers to this mentality own of homo sapiens and therefore, have the function of providing satisfaction to such subject of the knowledge own of the human being. We demonstrate that the theory of relativity is philosophically about the themes of the time determinations about the man and the struggle of this man against time and death . And that the discourse of the theory of relativity has as structure deep the mythologem of the myth of Zeus, and therefore it is an update to the demands and conditions of current truth of the myth of Zeus as a representation of the man who wins the time and is established as the center of the universe.